A reduction-sensitive thermo-responsive polymer: Synthesis, characterization, and application in controlled drug release. (April 2018) - Song, Li; Zhang, Bao; Jin, E; Xiao, Chunsheng; Li, Gao; Chen, Xuesi
Graphical abstract: Highlights: A novel kind of reduction and thermal dual-responsive copolymer PEG-DTPA was synthesized. The cloud point temperatures of copolymers was highly tunable. The copolymer was promising for use as reduction and thermal dual responsive drug carriers in cancer therapy. Abstract: Herein, a novel kind of reduction and thermal dual-responsive polymer was synthesized by direct condensation polymerization of poly(ethylene glycol) (PEG) and 3, 3′-dithiodipropanoic acid (DTPA). The resulting PEG-DTPA copolymers were soluble in water at room temperature and exhibited reversible thermal-responsive behaviors. The cloud point temperatures of PEG-DTPA copolymers were highly tunable dependent on the polymer concentration and the length of PEG segment. Additionally, the PEG-DTPA copolymers exhibited reduction-responsive behavior due to the presence of disulfide linkage groups in the backbone. This reduction-responsive property allowed the PEG-DTPA copolymers to be used in a drug delivery system. Thus, a triblock copolymer composed of mPEG2k and PEG400-DTPA copolymer was synthesized. The obtained copolymers could self-assemble into spherical micelles and exhibited thermal and reduction dual-responsive structure-variations in aqueous media. Furthermore, the hydrophobic Nile Red was effectively encapsulated into the micelles. The micelles maintained excellent reduction-responsive properties and can release drugs by reduction triggering. These results suggested that the PEG-DTPA copolymer may be promising for use as reduction and thermal dual-responsive drug carriers in cancer therapy.